Peningkatkan Efektivitas Layanan Pengaduan dengan Sistem Informasi Layanan Pengaduan Berbasis Web Mobile - Padiku, Indhitya Rahman; Takdir, Rahman; Paneo, Amirrudin (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2024)
UPT TIK's complaint service relies on manual methods such as physical mail and WhatsApp, resulting in challenges related to prioritization and limited technical personnel availability. To tackle these obstacles, the study advocates for the utilization of the Multi-Attribute Utility Theory as a decision-making approach. This method facilitates a thorough evaluation of various pertinent factors crucial in decision-making processes about complaint resolution. The development process of the complaint service information system adheres to the Prototype method. Initial phases entail extensive stakeholder engagement to gain profound insights into their needs and expectations regarding the new system. Subsequent meticulous planning aims to formulate effective implementation strategies. Following this, detailed system structure design is conducted to provide a comprehensive depiction of the system's architecture and functionality. Subsequently, prototype construction ensues, aimed at developing software aligned with the agreed-upon design. The final stage involves system delivery and feedback, where the developed system is disseminated for widespread implementation among end-users. User feedback serves as a valuable tool for making necessary improvements and adjustments. The implementation of this complaint service information system is anticipated to streamline the complaint resolution process, prioritize urgent complaints, and optimize the utilization of technical resources. This endeavor is poised to enhance the quality of information technology and communication services within the university setting, consequently yielding substantial benefits for the academic and administrative community as a whole. Additionally, the study also discusses practical implications and outlines directions for future research.